PASS theory of intelligence in Greek: A review - Papadopoulos, Timothy C. (Preschool and Primary Education, 2013)
This article reviews the research focusing on the application of the PASS (Planning, Attention, Simultaneous, and Successive) neurocognitive theory of intelligence (Das, Naglieri, & Kirby, 1994) in Greek. Studies that have used the Greek version of the Cognitive Assessment System (CAS; Naglieri & Das, 1997) and PREP (PASS Reading Enhancement Program) are reviewed. It is concluded that when the research is taken as a whole, with regard to the content, quality, and results of the pertinent correlational and intervention studies, the applications of PASS theory yield similar results to those deriving from other populations who differ in cultural and linguistic characteristics. Implications for future research are discussed.